CARBON TECHNOLOGY ACTIVE COCONUT SHELL ON AIR FILTER MEDIA FOR DOMESTIC WASTE AIR WASTE: PEMANFAATAN CARBON AKTIF TEMPURUNG KELAPA SEBAGAI MEDIA FILTER AIR UNTUK MENGATASI AIR TERCEMAR LIMBAH DOMESTIC - Dedy Khaerudin; Asep Rahmatullah (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
Clean availability air used when coming from wells (air land) for the needs of everyday residents, air conditions are very murky, yellow, sour and post-idanan from the pollution of domestic waste air from waste air laundry, bathroom, toilet waste and the rest of the rice field irrigation system, although currently Kp. Sendal Kopo, Panenjoan Village has a unit of clean air water is the top thing to treat the surrounding residents Community-Based Sanitation (Sanimas) from the central government is limited only dipoman air waste household results to irrigate rice fields, not for air needs One way in processing ground air by designing air filters from PVC pipes using activated carbon media from coconut shells and additional media foam filter, injury, zeolite stone, activated carbon and sand silica for air to make the air good air. Simple air filter everywhere in Kp.Sendal Kopo, Panenjoan Village, Carenang District, Serang District, Banten Province. Any activity there provides favours throughout the community Kp. Sendal Kopo, Village Panenjoan RT / RW: 004/01 involved in the workshop of making simple air filters and counselling will maintain and manage clean air so that with the village Of Panenjoan will be murky and political air into air that has standard air through clean air design intalasi air